Nobilamides A-H, Long-Acting Transient Receptor Potential Vanilloid-1 (TRPV1) Antagonists from Mollusk-Associated Bacteria - Lin, Zhenjian (2011)
New compounds nobilamides A-H and related known compounds A-3302-A and A-3302-B were isolated based upon their suppression of capsaicin-induced calcium uptake in a mouse dorsal root ganglion primary cell culture assay. Two of these compounds, nobilamide B and A-3302-A, were shown to be long-acting antagonists of mouse and human TRPV1 channels, abolishing activity for >1 h after removal of drug presumably via a covalent attachment. Other derivatives also inhibited the TRPV1 channel, albeit with low potency, affording a structure-activity profile to support the proposed mechanism of action. While the activities were modest, we propose a new mechanism of action and a new site of binding for these inhibitors that may spur development of related analogs for treatment of pain.